Perumusan Strategi Pada GIANT Supermarket Pulosari Malang Berdasarkan Quantitative Strategic Planning Matrix - NARDIYAH, FADHILAH PRASETYANINGTYASSAKTI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research was based on the importance of management strategy for the company and aims to formulate the right strategy in the face of business competition with other retail companies. The type of the research is descriptive research using the case study approach. Therefore, this study is to describe and explain the internal and external conditions affecting the company's management strategy. The analytical tool used in this research is the analysis of SWOT Matrix, Internal-External matrix (IE) dan QSPM matrix. From the known IE matrix is firm position on the cell I that can be described as growth and build and thestrategy is an intensive strategy, consisting of a strategy of market penetration, market development and product development strategy. And then from the SWOTmatrix obtained some alternative strategies that can be applied to company, that is SO strategy (Strengths Opportunity) consists of an intensive strategy andintegration strategy. Finally, the results of the analysis using QSPM matrix, it isknown that the right strategy to be implemented at the company was as IntensiveStrategies which is consist of Market Penetration, Market Development, and Product Development. Keywords: Functional Strategies, Internal Conditions, External Condition, SWOT matrix, IE matrix, QSPM matrix